Immobilized enzymes for nutraceuticals production (Nepal Journal of Environmental Science, 2023)
Due to the various advancements in enzyme development, enzymes have different applications in industries, agriculture, and medical field as well as to make various compounds or molecules. Immobilization refers to the combining the physico-chemical properties of enzyme with the carrier which will enhance the stability of any biocatalyst. The market of nutraceutical products is gaining wide importance. With this view, the present chapter here will focus on various immobilized enzymes with recent advances, and application of immobilized enzymes in production of various nutraceutical compounds. The nutraceutical compounds improve the flavour, structure and digestion of different food products. The immobilized enzymes can be capsulated which can be used effectively for nutraceuticals production. The use of immobilized enzymes for nutraceutical compounds is very eco-friendly, easy with sustainable approach.